Association between the metabolic score for insulin resistance (METS-IR) and arterial stiffness among health check-up population in Japan: a retrospective cross-sectional study - Liu, Gailing (Frontiers in Endocrinology, 2024)
Aim: This study examined the association between the metabolic score for insulin resistance (METS-IR), a novel surrogate indicator of insulin resistance, and brachial-ankle pulse wave velocity (baPWV) in Japanese health check participants.A cross-sectional research was conducted involving individuals in a program of medical health screening at the Medical Health Check-up Center in Japan. The study assessed the connection between METS-IR and baPWV in 912 participants who joined the program between 3/1/2004 and 12/31/2012. Serum laboratory tests and lifestyle surveys were the covariates. Multivariate linear regression analysis and subgroup analyses were performed.Results: 912 participants were involved in this cross-sectional study. Adjusted for age, sex, BMI, AST, UA, HDL, eGFR, ankle-brachial index (ABI), alcohol consumption, and smoking status, multivariate linear regression analysis showed that METS-IR and baPWV showed a significant positive association (adjusted β=15.3, 95% confidence interval (CI): 6.61 23.98) with METS-IR as a continuous variable. When converting METS-IR to quartile categorical variables, higher quartile METS-IR indices had longer baPWV (Q3 vs Q1, β=86.14, 95% CI: 23.45 148.83; Q4 vs Q1, β=125.41, 95% CI: 39.99 210.84). In subgroup analysis, METS-IR was associated with baPWV in people with eGFR > 60 ml/min (adjusted β= 14.